Afterlives of Revolution: Everyday Counterhistories in Southern Oman Alice Wilson (Stanford, CA: Stanford University Press, 2023). Pp. 336. $30.00 paper. ISBN: 9781503635784 - Lori, Noora (International Journal of Middle East Studies, 2025)
Keywords: Recension

La politica berbera nella Libia coloniale. Identità, reti e conflitti (1835-1924), Roma, Carocci, 2025, 166 pp. - Di Tolla, Anna Maria (Afriche e Orienti, 2026)
Keywords: Recension

Rive orientale de l'Arabie: hommes et espaces au début de l'islam / Moez Dridi. Éd. l'Harmattan, 2025 - Lochon, Christian (Mondes et Cultures : comptes rendus trimestriels des séances de l’Académie des sciences d’outre-mer, 2025)
Keywords: Recension

Contemporary Oman: The Sultan, the People, and the Legacy of Peace: By Mahjoob Zweiri and Farah AL Qawasmi (eds) (Berlin: Gerlach Press, 2025), viii + 263 pp., £90 (hardback), ISBN 978-3-95994-184-6 - Bradshaw, Tancred (Middle Eastern Studies, 2026)
Keywords: Recension

Oman’s Transformation after 1970 - Hughes, Geraint (Bustan: The Middle East Book Review, 2025)
Scholars and students of the history and politics of the Sultanate of Oman will in all likelihood acknowledge John E. Peterson as the doyen of their field, being active in the study of this Gulf state for just over fifty years. Oman’s Transformation after 1970 is a follow-up to his 2007 book Oman’s Insurgencies, which provided a detailed historical account of the Jebel Akhdar (1955–59) and Dhofar (1963–c.1976) rebellions and the counter-insurgency campaigns Sultans Said bin Taimur (1932–70) and Qaboos bin Said (1970–2020) waged with British support to defeat them.Over the past fifty-five years, Oman has evolved from an impoverished tribal state under Britain’s informal imperial influence to a fully sovereign, prosperous, but absolute monarchy. It has close ties to the Western powers and other members of the Gulf Co-operation Council (GCC), while playing an active role in regional diplomacy and preserving a semblance of neutrality (Oman has, for example, acted as a mediator between the US and the Islamic Republic of Iran and has tried to broker peace between the Houthis and their enemies in Yemen). Although the Sultanate did experience some internal unrest during the 2011 “Arab Spring” (442–44), it has not only emerged as one of the most stable states in the Middle East but also managed a peaceful transition of power after Qaboos’s death in January 2020. This was not an outcome that contemporary observers would have anticipated in the context of both Qaboos’s seizure of power in a palace coup in July 1970 or his regime’s struggle for survival against insurgent movements both in the Southern province of Dhofar and Northern Oman.1
Keywords: Recension

Afterlives of revolution: everyday counterhistories in southern Oman: by Alice Wilson, Stanford, CA, Stanford University Press, 2023, 336 pp., ISBN 978-1-5036-3578-4. - Alsraiha, Kassim (British Journal of Middle Eastern Studies, 2025)
Keywords: Recension

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Pierce, Stephen (African Studies Review, 2025)
Keywords: Recension

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Sabra, Adam (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2025)
Keywords: Recension

Aillet, Cyrille. L’archipel ibadite. Une histoire des marges du Maghreb médiéval. Collection Mondes Médiévaux. Lyon: CIHAM-Éditions, 2022. ISBN: 9782956842644. 592 pp. €45 paper. - Bosanquet, Antonia (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2025)
Keywords: Recension

Amal Sachedina, Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman:Cornell, Cornell University Press, 2021 274 pages - Ayachi, Mehdi (Critique internationale, 2025)
Keywords: Recension

Cyrille Aillet : L’archipel ibadite - une histoire des marges du Maghreb médiéval. - Hassen, Mohamed (Revue de l'Institut des Belles Lettres Arabes, 2024)
Keywords: Recension

Zanzibar was a Country: Exile and Citizenship between East Africa and the Gulf by Nathaniel Mathews (review) - Vartavarian, Mesrob (Global Black Thought, 2025)
Keywords: Recension

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval, CIHAM Éd., Lyon–Avignon, 2021 ; 1 vol., 582 p. (Mondes médiévaux, 5). ISBN : 978-2-95684-264-4. Prix : € 45,00 - Sénac, Philippe (Le Moyen Age, 2025)
Keywords: Recension

Britain and the Dhofar War in Oman, 1963–76: A covert war in Arabia: by Geraint Hughes, Basingstoke, Palgrave Macmillan, 2024, 325 pp, £119.99, ISBN 978-3-031-49498-7; The Dhofar War: British Covert campaigning in Arabia, 1965–75, by Stephen Quick, Exeter, University of Exeter Press, 2024, 235 pp, £95.00, ISBN 9781804130988. - Beckett, Ian F W (Small Wars & Insurgencies, 2025)
Keywords: Dhofar; Recension

Zanzibar Was a Country: Exile and Citizenship between East Africa and the Gulf By Nathaniel Mathews - Wint-Frederick, Hollian (Journal of Social History, 2025)
Tracing the lives, experiences, and ideas of Zanzibari Arabs through rich oral and written archives, Zanzibar Was a Country demonstrates the significance of “experiences in diaspora” to Indian Ocean postcolonial national belonging (2). Belonging, in Mathews’ rendering, refers to both “sentiment” —the idea of Zanzibar as a sovereign state and collective attachment to it—and citizenship—recognized political status and the infrastructures that produce it. The book makes two key intersecting interventions: first, by examining the political economy of citizenship from the era of developmental colonialism to the hydrocarbon-fueled developmentalism of the Arabian Gulf, Mathews presents an important analysis of decolonization as an economic process in which the tensions of the late colonial era continued. Second, he explores the complex and diverse articulations of Zanzibari-Omani belonging that emerged among diasporic Zanzibaris in this context, both in individual memory and through a vibrant vernacular historiography. This is a book that takes seriously not just the memories of its interlocutors, but their scholarship; their own endeavors in writing their history.
Keywords: Recension

Sovereigns of the Sea: Omani Ambition in the Age of Empire: by Seema Alavi - Chowdhary, Mir Kamruzzaman (Journal of the Indian Ocean Region, 2025)
Keywords: Recension

Hafed Abdouli, Min Trībūlīṭāniya ilā Aṭrābuls: al-mašhad al-ta‘mīrī ḫilāl al-‘aṣr al-wasīṭ al-mutaqaddam bayna al-tawāṣul wal-taḥawwulāt, [De la Tripolitaine à Tripoli : le paysage urbain au début du Moyen Âge entre continuité et changement]: Leyde, Brill, 2023 - Amara, Allaoua (Revue des mondes musulmans et de la Méditerranée, 2025)
Keywords: Recension

Zanzibar was a country: exile and citizenship between East Africa and the Gulf: Nathaniel Mathews, Oakland, CA, University of California Press, 2024, 358 pp., $29.95/£25.00 (paperback), ISBN: 9780520400702 - Nicholson, Timothy (Global Change, Peace & Security, 2025)
Keywords: Recension

Miranda Morris, Ethnographic Texts in the Baṭḥari Language of Oman - Rubin, Aaron D. (Journal of Semitic Studies, 2025)
Keywords: Linguistique -- Oman; Recension

Résistance et Dévotion. Anciens sanctuaires ibadites de Djerba - Chekhab-Abudaya, Mounia (Bulletin critique des Annales islamologiques, 2025)
Résistance et Dévotion : Anciens sanctuaires ibadites de Djerba, publié par Virginie Prevost, est le fruit d’un long travail commencé en 1996 et enrichi, depuis 2009, des clichés du photographe Axel Derriks. Cet ouvrage se présente comme une étude historique et architecturale minutieuse portant sur quarante-huit mosquées de l’île de Djerba, avec pour dessein de « conserver la mémoire des anciens lieux de culte de Djerba » (p. ix). Tout au long du volume, V. Prevost souligne de manière pertine...
Keywords: Architecture -- Djerba; Recension

Min Trībūlītānyā ilā Aṭrābulus : al-mashhad al-taʻmīrī khilāl al-ʻaṣr al-wasīṭ al-mutaqaddam bayn al-tawāṣul wa-l-taḥawwalāt من تريبوليتانيا إلى أطرابلس المشهد التعميري خلال العصر الوسيط المتقدّم بين التواصل والتحوّلات - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2025)
Voici la première monographie publiée par le chercheur tunisien Hafed Abdouli, tirée en partie de sa thèse de doctorat consacrée à la Tripolitaine médiévale, défendue à Tunis en 2011 sous la direction de Faouzi Mahfoudh. L’ouvrage, préfacé par Ahmed M’Charek, constitue le premier volume d’une nouvelle collection des éditions Brill, Libya Islamica, et s’inscrit dans un intéressant programme de recherches dirigé par Aurélien Montel et Sébastien Garnier, Libmed, qui propose, sous la forme d’un s...
Keywords: Recension

Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman: Amal Sachedina - Chatty, Dawn (Journal of Arabian Studies, 2025)
Keywords: Recension

سردية الخرافة الشعبية الأمازيغية: قراءة في كتاب حكايات أمازيغية لفتحي بن معمر - ضو, سليم (Revue de l'Institut des Belles Lettres Arabes, 2023)
نهتمُّ في هذا المقال بدراسة لون من الأدب الشعبي هو الخرافة الشعبيّة الأمازيغيّة، وذلك بالبحث في بنيتها –أي الخرافة الشعبية- وخصائصها ومميزاتها التي بها تتفرّد عن سائر أنماط الأدب الشعبي الأخرى على غرار الأحاجي والأمثال وأغاني النساء... والنظر في القوانين التي من خلالها تنتظمُ، لغرض الوقوف على ملامح سرديّتها وأدبيّتها. وذلك من خلال تركيز النظر على مُدوّنة تونسيّة أثْرت بوضوح الأدب الشعبيّ التونسي، وأسهمت في نفض الغبار عن ثقافة محليّة مغمورة –نعني الثقافة الأمازيغيّة- يلفّها الكثير من النسيان والإغفال ويتهدّدها الاضمحلال جرّاء تراجع نسبة الناطقين بها لاعتبارات عديدة، ونقصدُ بذلك مجموعة "حكايات أمازيغيّة جربيّة" الكاتب التونسي من أصل أمازيغي فتحي بن معمر (1967). وتنخرطُ مجموعته هذه ضمن مشروع ثقافي كان قد انطلق فيه منذ سنوات يهدفُ إلى تجميع المادّة التراثية الأمازيغيّة الشفهيّة وتوثيقها ونشرها للتعريف بها لدى الأجيال الجديدة ولحمياتها من كل أشكال الطّمس والتغييب والسطو عليها. وسيكون تركيزنا خلال هذا المقال مُنصبًّا على فحص الخصائص الأجناسيّة لهذه النصوص ووظائفها، وذلك بالانطلاق بدراسة بنية هذه الحكايات الخارجيّة والداخليّة أي البنية القصصية المتكونة من اُطر وفواعل وأحداث، مرورا بالبحث في الشخصيات وأصنافها ووظائفها مستفيدين في ذلك من المنهج المورفولوجي لفلاديمير بروب، ثمّ التعريج على خصائص الأُطر الزمانية والمكانية، اِنتهاءً بالمواضيع والقضايا التي أثارتها هذه القصص. ثمّ في عُنصر لاحق لجأنا إلى رصد جُملة الوظائف التي تؤدّيها هذه الحكايات والتي منها ما يتعلّقُ بالراوي ومنها ما يتعلق بالمروي لهُ.
Keywords: Littérature -- Djerba; Recension

L'archipel ibadite - une histoire des marges du Maghreb médiéval - Mohamed, Hassane (Revue de l'Institut des Belles Lettres Arabes, 2024)
Keywords: Recension

Islam, réforme et colonisation: Une histoire de l’ibadisme en Algérie (1882-1962) - Cherih, Chaouki (Revue d'histoire moderne contemporaine, 2024)
Keywords: Recension

Alice Wilson, Afterlives of Revolution. Everyday Counterhistories in Southern Oman - Boulay, Sébastien (L’Homme. Revue française d’anthropologie, 2024)
Ce n’est pas la première fois qu’Alice Wilson nous invite à découvrir un mouvement révolutionnaire du monde arabo-musulman et ses réminiscences dans le présent. Notre collègue de l’Université de Sussex au Royaume-Uni s’était en effet déjà fait connaître en 2016 par un ouvrage consacré au mouvement de libération du Sahara occidental, le Front Polisario, et à la République arabe sahraouie démocratique, dans lequel elle se penchait sur la question de la souveraineté exercée par cet État exilé de...
Keywords: Recension

A Review of “Persistent Pastoralism: Monuments and Settlements in the Archaeology of Dhofar” - Mosapour Negari, Fariba (Iranian Journal of Archaeological Studies, 2024)
Keywords: Recension

New Materials on Ibāḍism in Iraq and Arabia at the Second and Third Centuries of Islam. Review of Al Salimi & Madelung, Ibāḍī Texts from the 2nd/8th Century (Leiden: Brill, 2018); Al Salimi, Ibadi Texts in Oman from the 3rd/9th Century (Leiden: Brill, 2021) - Baptiste, Enki (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2024)
Keywords: Recension

Recent Trends in the Studies of Ibadism in North Africa - Abdelfattah, Sami Samir (International Journal of Academic Research in Business and Social Sciences, 2024)
Keywords: Recension

Cheriau Raphaël, Intervention d’humanité. La Répression de la traite des esclaves à Zanzibar, années 1860-1900, Paris, CNRS Éditions, 2023, 400 p. ISBN 978-2-271-12720-4, 27 euros. - Frémeaux, Jacques (Outre-Mers, 2024)
Keywords: Recension

قراءة نقدية في كتاب الخطب المنبرية للشيخ إبراهيم بن محمد طلاى - بن دريسو, مصطفى بن محمد (‏الملتقى الدولي الشيخ إبراهيم طلاي وإسهاماته الحضارية, 2024)
Keywords: Recension

Cyrille Aillet, L’archipel Ibāḍīte. Une histoire des marges du Maghreb médiéval, Lyon, CIHAM Éditions, 2022 - Francesca, Ersilia (Der Islam, 2024)
Article Cyrille Aillet, L’archipel Ibāḍīte. Une histoire des marges du Maghreb médiéval, Lyon, CIHAM Éditions, 2022 (Mondes médiévaux). 592 p. ISBN: 978-2-9568426-4-4. was published on October 1, 2024 in the journal Der Islam (volume 101, issue 2).
Keywords: Recension

Virginie Prevost, Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe–XIIIe siècle), Monograph 10, London: Society for Libyan Studies, 2016, 232 pp., ISBN 978 1 900971 41 6. - Gutiérrez, González Carmen (Der Islam, 2024)
Keywords: Recension

PAUL M. LOVE Jr. The Ottoman Ibadis of Cairo: A History (Cambridge: Cambridge University Press, 2023). 236pp., $105.55 cloth. ISBN: 9781009254267. - Gaiser, Adam R. (Review of Middle East Studies, 2024)
Keywords: Recension

مستقبل سلطنة عمان بعد السلطان قابوس (مجلة كلية القانون والعلوم السياسية, 2024)
Keywords: Recension

مقاصد الشريعة عند الإمام نور الدين السالمي: قراءة في أطروحة د/ صالح عبد الرحمان - قشار, عمر بن بالحاج (2024)
Keywords: Recension

Ship Timbers from the Islamic Sites of al-Balid and Qalhat, Oman: Sewn-Plank Technology in the Indian Ocean during the 10–16th Centuries CE: Nautical Archaeology Society Monograph Ser. (NAS) 7, BAR International Series 3132, by Alessandro Ghidoni, Oxford, UK, BAR Publishing, 2023, 189pp., numerous illustrations, some colour, £58.00 (sbk), ISBN 9781407360577 - Zazzaro, Chiara (International Journal of Nautical Archaeology, 2024)
Keywords: Archéologie -- Oman; Recension

Ritter Stefan, Ben Tahar Sami (éd.), Studies on the Urban History of Meninx (Djerba). The Meninx Archaeological Project, 2015–2019 (Archäologische Forschungen, 43), Wiesbaden, DAI-Reichert, 2022, 1 vol. 21 × 30, Volume I, 454 p. + 11 pl., 248 fig. n/b et coul., ISBN : 978-3-75200-611-7. - Bejaoui, Fathi (Revue archéologique, 2024)
Keywords: Archéologie -- Djerba; Recension

Adam R. Gaiser, Sectarianism in Islam: The Umma Divided, Themes in Islamic History, xii, 237 pp., Cambridge: Cambridge University Press, 2023, ISBN 9781009325042. - Bernheimer, Teresa (Der Islam, 2024)
Keywords: Recension

L’archipel ibadite. Une histoire des marges du Maghreb médiéval, written by Cyrille Aillet - Love Jr, Paul M. (Arabica, 2024)
Keywords: Recension

Review of Local and Global Identities, (Studies on Ibadism and Oman 13) - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2020)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’Ibadisme en Algérie (1882-1962) - Pace, Enzo (Archives de sciences sociales des religions, 2021)
Quel a été l’impact du colonialisme français sur ce que nous appelons sommairement l’islam ? Et en particulier sur les complexes relations que cette religion a nouées, au cours des années, avec les principales institutions sociales et politiques dans l’un des plus grands pays du Maghreb, l’Algérie ? Comment la domination coloniale a-t-elle été vécue et interprétée par les organes intellectuels du savoir et du pouvoir religieux musulman ? De manière passive, en subissant les effets inattendus ...
Keywords: Recension

Cultivating the past, living the modern: the politics of time in the Sultanate of Oman - Eldridge, Aaron F. (Politics, Religion & Ideology, 2024)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962), Paris, Éditions de la Sorbonne, « Bibliothèque historique des pays d’Islam », 2020, 398 p. - Perrier, Antoine (Le Mouvement Social, 2023)
Keywords: Recension

Abdulrahman Al-Salimi and Eric Staples, eds., Oman: A Maritime History. Studies on Ibadism and Oman , vol. 9, Hildesheim: Georg Olms Verlag, 2017. - Bahl, Christopher (Der Islam, 2023)
Keywords: Recension

Adam R. Gaiser: Sectarianism in Islam: The Umma Divided (Themes in Islamic History.) xii, 237 pp. Cambridge: Cambridge University Press, 2023. £70. ISBN 9781009325042. - Anchassi, Omar (Bulletin of the School of Oriental and African Studies, 2023)
Keywords: Recension

Zimmermann, Wolfgang et Gabriele Goldfuß, Magisches Musandam : Omans ferner Norden - Klinger, Thibaut (Arabian Humanities, 2023)
C’est un livre singulier que vient de publier au soir de sa carrière le géographe Wolfgang Zimmermann, associé à Gabriele Goldfuß, son épouse, universitaire spécialiste du bouddhisme, aux éditions allemandes Georg Olms, qui édite notamment la série d’ouvrages Studies on Ibadism and Oman. Le titre Magisches Musandam : Omans ferner Norden (Musandam magique : l’extrême Nord d’Oman) pourrait être celui d’un coffee-table book selon la terminologie anglo-saxonne : s’il présente près de 200 photogra...
Keywords: Recension

Fathi Ben Maammar, Tinfas seg Jerba - Ḥikāyāt amāzīghiyya jarbiyya - Brugnatelli, Vermondo (Journal of Amazigh Studies, 2023)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962). Paris, Éditions de la Sorbonne, 2020. 397 pp. €35.00 (pb). ISBN 979-10-351-0532-7. - Messaoudi, Alain (H-France Review, 2022)
Keywords: Recension

The Collective Biography of a Muslim Community - Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr. Cambridge: Cambridge University Press, 2018. Pp. xxi + 206. 80.00, hardcover (ISBN: 9781108472500). - Hall, Bruce S. (The Journal of African History, 2021)
Keywords: Recension

Book Review: "Sultan Qaboos and Modern Oman, 1970-2020" by Allen James Fromherz and Abdulrahman al-Salimi, eds. - Junyent, Marc Martorell (Manara Magazine, 2022)
Keywords: Recension

Portugal in the Sea of Oman. Religion and Politics. Research on Documents, edited by Abdulrahman Al-Salimi and Michael Jansen and in collabaration with Pedro Pinto, Karsten Ley, and Helmut Siepmann - Biedermann, Zoltán (Journal of Early Modern History, 2021)
Keywords: Recension

الاقلية الذاتية للمنزابيين في الفترة الاستعنارية عزض ومناقشة: الجزء الأول - خواجة, عبد العزيز بن محمد (2022)
Keywords: Recension

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2023)
Voici enfin une monographie consacrée aux ibadites du Maghreb, depuis leur origine jusqu’au xve siècle, présentée en 2018 pour l’habilitation à diriger des recherches de Cyrille Aillet. Elle comprend onze chapitres, une chronologie, une vaste bibliographie et plusieurs index, notamment un très utile index des notions. Signalons, c’est assez peu courant, que l’index des personnes reprend aussi les noms des auteurs contemporains. Le livre retrace l’histoire des ibadites maghrébins et a pour obj...
Keywords: Recension

Book Review: “The Ibadi presence in Egypt” | مراجعة كتاب: الوجود الإباضي في مصر - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
The cover of al-Wujūd al-Ibāḍī fī Miṣr (Maktabat Khazāʾin al-Āthār, 2018). I borrow the image here from a remarkably detailed summary of the book available in Arabic here. I recently had the pleasu…
Keywords: Recension

Vient de paraître: Djerba, l’île enchantée … - Hamza, Alya (La Presse de Tunisie, 2020)
« Djerba, l’île enchantée »  répond, certes, aux critères de « Beau Livre », de par l’élégance de sa présentation, la beauté de ses photos, le soin de sa
Keywords: Recension

Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962), written by Augustin Jomier - Francesca, Ersilia (Studia Islamica, 2022)
Keywords: Recension

Cyrille Aillet, L’ibadisme dans les sociétés de l’Islam médiéval. Modèles et interactions - Rebstock, Ulrich (Die Welt des Islams, 2022)
Keywords: Recension

Uṣūl al-Dīn (The Fundamentals of the Faith). By Tibghūrīn b. īsā al-Malshūṭī. Edited by 'Amr Khalifa Ennami and translated into English by Trevor Le Gassick - Gaiser, Adam R. (Journal of the American Oriental Society, 2022)
Keywords: Foi -- Traité -- 12e siècle; Malshūṭī, Tibghūrīn b. ʿĪsā al-; Recension

Hannah-Lena Hagemann: The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. (Edinburgh Studies in Classical Islamic History and Culture.) xii, 328 pp. Edinburgh: Edinburgh University Press, 2021. £85. ISBN 978 1 4744 5088 1. - Kenney, Jeffrey T. (Bulletin of the School of Oriental and African Studies, 2022)
Keywords: Recension

Islam, réforme et colonisation: Une histoire de l’ibadisme en Algérie (1882–1962) - Chih, Rachida (The Journal of North African Studies, 2022)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr - Ghazal, Amal N. (Journal of Islamic Studies, 2021)
Typically, siyar in the Islamic tradition are biographical texts outlining the life and times of individuals, whether scholars or otherwise. Siyar are not known to offer coherent historical narratives, nor are they complete historical chronicles. They are usually compiled in an incremental manner, passing from one generation to another, creating a chain of individuals and/or communities across time and space. Despite their prominence, they have mostly served the historical profession, more or less, as biographical dictionaries. Ibadi siyar in North Africa belong to this same genre and have served a similar purpose. Paul Love’s book uses an innovative methodology in his analysis of siyar that changes the way historians can use and read these texts.
Keywords: Recension

Islam, réforme et colonisation: une histoire de l'ibadisme en Algérie, 1882–1962 by Augustin Jomier - Brower, Benjamin Claude (Arab Studies Journal, 2022)
Keywords: Recension

Al-Salimi, Abdulrahman: On the Reception of Early Ibadi Theology. A Commentary on the Book on Monotheism by ‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century). - Metzler, Berenike (Orientalistische Literaturzeitung, 2022)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Ismail Albayrak, Approaches to Ibāḍī Exegetical Tradition - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2022)
Ismail Albayrak is Professor at the Australian Catholic University in Melbourne. He has been studying Islamic theology and exegesis for two decades. This present book deals with the little-known field of Ibadi studies. Scholars are increasingly beginning to appreciate Ibadi materials as these sources offer new perspectives to understand the formative period of Islam. The texts produced by the communities either in North Africa or in Arabian Peninsula are better known and most of them are now ...
Keywords: Recension

Paul Love, Ibadi Muslims of North Africa. Manuscripts, Mobilization, and the Making of a Written Tradition - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2021)
Paul Love, actuellement Assistant Professor à l’Université d’Al Akhawayn (Ifrane, Maroc), est un spécialiste de l’histoire de l’ibāḍisme médiéval au Maghreb. Dans cet ouvrage, il livre le fruit de ses recherches de doctorat. L’ibāḍisme ne cesse d’attirer de nouveaux chercheurs et les récentes publications sur l’histoire de ces groupes religieux disséminés dans les marges de l’Empire islamique témoignent de la richesse du corpus de sources à explorer. Les sources ibāḍites maghrébines, que l’on...
Keywords: Recension

Cyrille Aillet (éd.), L’ibadisme dans les sociétés de l’Islam médiéval. Modèles et interactions - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2020)
L’ibāḍisme reste le parent pauvre des études d’islamologie et d’histoire des mondes musulmans médiévaux. Cet ouvrage est néanmoins une contribution supplémentaire à l’important chantier de renouvellement des études portant sur les sociétés ibāḍites maghrébines et orientales prémodernes. Désormais mieux connue grâce aux travaux pionniers de J. Wilkinson, de P. Crone et, plus récemment, de C. Aillet et d’A. Gaiser, cette école juridique, parfois considérée comme la troisième branche de l’islam,...
Keywords: Recension

Rose Jeffrey I., Hilbert Yamandu H., Marks Anthony E., Usik Vitaly I. 2019. The first peoples of Oman. Palaeolithic archaeology of the Nejd plateau - Groucutt, Huw S. (Paléorient, 2020)
The Dhofar region in the southwest of Oman is a peculiar, and special, corner of Arabia. It represents the eastern-most extent of the highland spine of Arabia which extends down the west coast and then swings eastwards through Yemen. Traditionally Dhofar had more to do with areas to its west than to the rest of Oman, with social and linguistic connections to areas in modern-day Yemen. Likewise, Dhofar is a primarily Sunni Muslim area in contrast to the Ibadism dominant in the north of Oman. T...
Keywords: Recension

“Switzerland of Arabia”: Omani Foreign Policy and Mediation Efforts in the Middle East - Worrall, James (The International Spectator, 2021)
In recent years, Oman has been recognised as a key mediator in the Gulf and the wider Middle East. The successful completion of the 2015 Iran nuclear deal, in particular, firmly cemented its reputation as a peacemaker. To fully understand Omani mediation practices in the region, Muscat’s mediation must be placed within the context of the Sultanate’s wider foreign policy, and all known mediations must be assembled in one place in order to develop a typology to better understand forms and patterns. Ultimately, mediation both serves and is enabled by the Sultanate’s foreign policy. This was not an inevitable outcome. Over the course of Qaboos’ reign, Oman has developed into an ‘Interlocutor State’, in which the practice of mediation has become an important tool in furthering the central goals of preserving Oman’s independent foreign policy, and thus ultimately the Sultanate’s sovereignty and security itself.
Keywords: Recension

Review: A Maritime Lexicon Arabic Nautical Terminology in the Indian Ocean - Acevedo, Juan (Rutter Book Review, 2020)
Keywords: Recension

Cuperly Pierre, Toute Langue dit Dieu. Textes réunis et édités par Yacine Daddi Addoun and Soufien Mestaoui, Ibadica Geuthner, Paris 2020, Culture et Société, 303 pp. + 39 pp. in Arabic; Théologie ibâḍite, 226 pp. + 75 pp. in Arabic. - Fitzgerald, Michael L. (Islamochristiana, 2020)
Keywords: Recension

PREVOST, Virginie. Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siècle). London: Society for Libyan Studies Monograph 10, 2016, 231 páginas - Meouak, Mohamed (Miscelánea de estudios árabes y hebraicos, 2020)
Keywords: Recension

Ibadi Texts for the 2nd/8th Century - Rizvi, Sajjad (The Muslim World Book Review, 2020)
A quarterly publication of the Islamic Foundation, Markfield, Leicestershire, UK. This journal aims to present the Muslim viewpoint on books and issues which concern Islam and Muslims.
Keywords: Recension

Shurāt Legends, Ibāḍī Identities: Martyrdom, Asceticism, and the Making of an Early Islamic Community, written by Adam R. Gaiser, 2016 - Sahner, Christian C. (Islamic Law and Society, 2020)
"Shurāt Legends, Ibāḍī Identities: Martyrdom, Asceticism, and the Making of an Early Islamic Community, written by Adam R. Gaiser, 2016" published on 06 Aug 2020 by Brill.
Keywords: Recension

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, written by Abdulrahman al-Salimi - Benkheira, Mohammed Hocine (Studia Islamica, 2020)
Keywords: Recension

Review of The Ports of Oman - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Review of Today's Perspectives on Ibadi History - Jomier, Augustin (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Cyrille Aillet, Patrice Cressier, Sophie Gilotte (éd.), Sedrata. Histoire et archéologie d’un carrefour du Sahara médiéval à la lumière des archives inédites de Marguerite van Berchem: Madrid, Casa de Velázquez (« Collection de la Casa de Velázquez », 161), 2017, 497 p. - Mesnil, Emmanuelle Tixier du (Médiévales, 2020)
Keywords: Archéologie -- Sedrata; Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1931) - Richaud, Jean-David (Lectures, 2020)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition, by Paul M. Love - Prevost, Virginie (The English Historical Review, 2020)
This interesting and concise book finds its origin in Paul Love’s doctoral thesis defended in 2016 at the University of Michigan. It presents an innovative study of medieval Ibadi North-African Siyar. In the Maghrib, Siyar are books containing anecdotal and biographical information about individuals, playing the role of chronicle-style history; they function as prosopographies, collective biographies in which stories about individual members come together to form the biography of the community, constructing a North-African Ibadi tradition (p. xx). Love’s book tells the story of the compilation, adaptation and circulation of that prosopographical corpus through five scholars’ works. The pioneer is Abû Zakariyyâ’ al-Wârjalânî who provided Ibadi scholars of the second part of the eleventh century with a cohesive narrative of their history, when the community was suffering an ongoing numerical decline; he chose to write in the Arabic language at a time when use of the Berber language was also in decline. The author then studies the works of al-Wisyânî, al-Darjînî and al-Barrâdî. The last Ibadi scholar is al-Shammâkhî (d. 1522), who compiled all of the biographies of his predecessors into one collection and brought that medieval tradition of Ibadi prosopography to a close.
Keywords: Recension

L’ibadisme dans les sociétés de l’islam médiéval: Modèles et interactions: edited by Cyrille Aillet - Hoffman, Valerie J. (Islam and Christian–Muslim Relations, 2020)
Keywords: Recension

Reviewed Work: The Ports of Oman by Abdulrahman Al Salimi/Erich Staples - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Al Salimi, Abdulrahman and Staples, Eric: A Maritime Lexicon. Arabic Nautical Terminology in the Indian Ocean. English-Arabic Edition. Hildesheim/Zürich/New York: Georg Olms Verlag 2019. 641 S. m. 341 Abb. 4° = Studies on Ibadism and Oman. Vol. 11. Hartb. € 88,00. ISBN 978-3-487-15393-3. - Müller, Walter W. (Orientalistische Literaturzeitung, 2020)
Keywords: Recension

Review of Oman. A Maritime History - Gemeinhardt-Buschhardt, Konstanze (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition by Paul M. Love, Jr. (review) - Propst, Amanda (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2020)
Keywords: Recension

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, edited by Al-Salimi, Abdulrahman - Francesca, Ersilia (Studi Magrebini, 2020)
Keywords: Recension

O[ma]n Ibadism and Modernity - Rebstock, Ulrich (Die Welt des Islams, 2020)
"O[ma]n Ibadism and Modernity" published on 27 May 2020 by Brill.
Keywords: Recension

The First Compendium of Ibadi Law. The “Mudawwana” by Abu Ghanim Bishr b. Ghanim al-Khurasani, written by Miklos Muranyi, 2018 - Rebstock, Ulrich (Die Welt des Islams, 2020)
Keywords: Fiqh -- Libye -- 8e siècle; Recension

Abdulrahman Al-Salimi and Eric Staples: A Maritime Lexicon: Arabic Nautical Terminology in the Indian Ocean. (Studies on Ibadism and Oman.) 641 pp. Hildesheim: Georg Olms Verlag, 2019. $98. ISBN 978 3 487 15393 3. - Bishara, Fahad Ahmad (Bulletin of the School of Oriental and African Studies, 2020)
Keywords: Recension

Kahlan Al-Kharusi (ed.): Āthār al-Rabīʿ b. Ḥabīb. Edition and Study. (Abhandlungen für die Kunde des Morgenlandes im Auftrag der Deutschen Morgenländischen Gesellschaft.) x, 172 pp. Wiesbaden: Harrassowitz, 2016. ISBN 978 3 447 10634 4. - Francesca, Ersilia (Bulletin of the School of Oriental and African Studies, 2020)
Keywords: Recension

Introduction à l’étude de l’ibāḍisme et de sa théologie, written by Pierre Cuperly - Di Tolla, Anna Maria (Annali dell'Istituto Universitario Orientale di Napoli, 2020)
Keywords: Recension